Kajian Literasi Kebencanaan Koleksi Perpustakaan Nasional - Retno Andini; Suharyanto Suharyanto (Ikatan Pustakawan Indonesia, 2022)
This paper describes the definition of disaster, disaster data throughout 2020, the National Library as a center of knowledge that presents various kinds of scientific subjects. This research method uses a description method based on the online catalog data of the national library opac.perpusnas.go.id. The results showed that the national library had disaster literacy of 1,594 titles with various types of collections, such as monographs, electronic sources, cartographic materials, manuscripts, and so on.